Abiotic stress tolerance in wheat with emphasis on drought - Ahad, Arzoo; Arshad, Manal; Ahmad, Namrah; Ilyas, Mahnoor; Batool, Tuba Sharf; Ejaz, Mahnoor; Gul, Alvina; Ozturk, Munir (Journal of Cereal Research, 2025)
Environmental change presents a significant hazard to most tropical and subtropical crops across the world. Drought stress is among the negative repercussions of environmental modification that affects agricultural development and output. It has a significant influence on the vegetative and propagative phases of plants. Considering the current and prospective nutrition demands of a growing populace, it is critical to target crop production in drought-prone rainfed areas. Crops respond to drought stress in various manners, including structural, physio-chemical, and molecular responses. Drought tolerance encompasses processes that operate at several geographical and temporal dimensions, ranging from immediate stomatal closure to crop production management. There are multiple genes in wheat that are responsible for drought resistance and generate various enzymes and proteins under drought conditions. This review focusses the current advances in wheat physio-chemical, and molecular adaptation to drought tolerance. The experimental data revealed that drought stress negatively impacts multiple physiological processes that occur in wheat plants during their various growth phases, including germination, vegetative growth, reproductive development, and maturity. Therefore, studying the drought-induced damage in wheat plants, as well as strategies for boosting drought tolerance, is critical for increasing wheat output. Furthermore, molecular genetics and breeding strategies for developing drought tolerance in wheat to boost yield and quality are discussed